2013
DOI: 10.1603/ec13268
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thiamethoxam Seed Treatments on Soybean Aphid (Hemiptera: Aphididae) Feeding Behavior

Abstract: Since its discovery in North America in 2000, the soybean aphid, Aphis glycines Matsumura (Hemiptera: Aphididae), has rapidly become an important pest of soybean [Glycine max (L.) Merrill], sometimes resulting in significant yield losses. Previous research has documented the toxicity of neonicotinoid seed treatments to soybean aphids, but control under field conditions has been inconsistent. Imidacloprid, a popular neonicotinoid insecticide, has been shown to exhibit antifeedant effects on aphids. Antifeedant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…Even with a decline in insecticidal activity, a substantial amount of time would be needed for the aphid population to reach damaging levels. Similarly, other studies have reported significant soybean aphid mortality within 1–4 days of exposure to neonicotinoid‐treated soybeans …”
Section: Discussionsupporting
confidence: 54%
“…Even with a decline in insecticidal activity, a substantial amount of time would be needed for the aphid population to reach damaging levels. Similarly, other studies have reported significant soybean aphid mortality within 1–4 days of exposure to neonicotinoid‐treated soybeans …”
Section: Discussionsupporting
confidence: 54%
“…At the completion of the starvation period, wired aphids were placed on the adaxial side of the newest, fully developed leaf. Aphid placement was considered successful if the individual was able to move freely on the leaf surface [46]. Plants on which no feeding occurred or for which no reliable signals were obtained were not included in further analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Plants on which no feeding occurred or for which no reliable signals were obtained were not included in further analyses. All plants, EPG probes, and plant electrodes were placed inside one of two Faraday cages, constructed from aluminum mesh wire with an aluminum frame and base (61 cm×61 cm×76 cm), in order to protect the EPG's internal conductors from electrical and environmental noise [10,46]. Recordings were made on eight plants simultaneously, with at least one plant of each of the three switchgrass populations represented in each recording.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations